PENGARUH PERSONAL BRANDING OWNER DAN STRATEGI PEMASARAN MELALUI INSTAGRAM MANGKOKKU TERHADAP MINAT BELI - Tarigan, Arihta; Kembau, Agung Stefanus; Setiawan, Sean Nicholas; Wijaya, Hubert; Chandra, Steven (ULTIMA Management, 2024)
Abstract - The purpose of this research is to see the influence of owner branding and marketing strategies via Instagram social media on buying interest in Mangkokku, where one of the founders of Mangkokku is Kaesang Pangarep who is the son of the president of the Republic of Indonesia. The number of respondents in this study was 100 and lived in Tangerang. The variables of this research include the personal branding of Mangkokku owner Kaesang Pangarep and also the marketing strategy via Mangkokku's Instagram account. This research uses a quantitative approach method by distributing questionnaires and processing the data using the SPSS application. This research concludes that the personal branding of the owner of Mangkokku does not influence people's buying interest in Tangerang City, but marketing strategies using social media Instagram influence people's buying interest in Tangerang City. Thus, to influence purchasing interest, Mangkokku must focus more on marketing strategies through social media, rather than just displaying the personal branding image of Kaesang Pangarep. Keyword : Instagram; Personal Branding; Retail Marketing; Social Media